2022
DOI: 10.3390/molecules27123734
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Lewis Pairs in Heterogeneous Catalysis: Theoretical Insights

Abstract: Frustrated Lewis pair (FLP) catalysts have attracted much recent interest because of their exceptional ability to activate small molecules in homogeneous catalysis. In the past ten years, this unique catalysis concept has been extended to heterogeneous catalysis, with much success. Herein, we review the recent theoretical advances in understanding FLP-based heterogeneous catalysis in several applications, including metal oxides, functionalized surfaces, and two-dimensional materials. A better understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Catalysis by FLPs is a new and vibrant field. The basic premise is that a sterically hindered Lewis acid and base pair can provide an active site that polarizes a molecule such as H 2 , leading to its dissociation and formation of protonic and hydridic species. , This FLP mechanism, originally suggested in homogeneous catalysis, has recently found numerous applications in heterogeneous catalysis. Since an FLP typically consists of an electron-rich and an electron-poor species, , it is not immediately clear how Gr can provide FLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysis by FLPs is a new and vibrant field. The basic premise is that a sterically hindered Lewis acid and base pair can provide an active site that polarizes a molecule such as H 2 , leading to its dissociation and formation of protonic and hydridic species. , This FLP mechanism, originally suggested in homogeneous catalysis, has recently found numerous applications in heterogeneous catalysis. Since an FLP typically consists of an electron-rich and an electron-poor species, , it is not immediately clear how Gr can provide FLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is also more conducive to the design and development of heterogeneous FLP catalysts. [24]…”
Section: Key Aspects Of Flp Catalytic Hydrogenationmentioning
confidence: 99%
“…Understanding the interaction of Lewis acid and Lewis base, as well as the mechanism of FLP activation of hydrogen source, is crucial for the study of hydrogenation reaction over FLP catalysts. Meanwhile, it is also more conducive to the design and development of heterogeneous FLP catalysts [24] …”
Section: Key Aspects Of Flp Catalytic Hydrogenationmentioning
confidence: 99%
“…As far as our knowledge, the first case of constructing heterogeneous FLPs is reported by Sautet and co-workers, where the nonadjacent Al···O pairs on the γ-alumina surface with both strong acidity and basicity are highly active for the heterolytic splitting of both H 2 and CH 4 . , Subsequently, Singh and co-workers reported that the In···O FLPs constructed on hydroxylated indium oxide surface with oxygen vacancies can effectively catalyze H 2 dissociation and following CO 2 hydrogenation. Recently, solid FLPs constructed by regulation of surface oxygen vacancies on reduced CeO 2 surfaces were proposed for hydrogen dissociation and methane conversion. ,, The enhanced FLP acidity and basicity together with the elongated distance of Ce···O pairs contribute to the high activity of the solid FLPs for hydrogen dissociation and acetylene hydrogenation . Besides oxide surfaces, designing heterogeneous FLPs has been proved by various strategies and materials, , such as functionalizing metal–organic framework (MOF), ,, adsorbing molecules on solid surfaces and doping two-dimensional materials. , Despite these significant advances in designing heterogeneous FLPs, metal elements are still indispensable for the construction of heterogeneous FLPs, which deviates from the initial metal-free concept of FLP catalysis . Therefore, it is imperative to develop metal-free heterogeneous FLPs which retain the high activity for hydrogen dissociation and match the original conception of FLPs as metal-free catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…19,30,31 The enhanced FLP acidity and basicity together with the elongated distance of Ce•••O pairs contribute to the high activity of the solid FLPs for hydrogen dissociation and acetylene hydrogenation. 19 Besides oxide surfaces, 32−37 designing heterogeneous FLPs has been proved by various strategies and materials, 23,38 such as functionalizing metal− organic framework (MOF), 20,39,40 adsorbing molecules on solid surfaces 41−43 and doping two-dimensional materials. 44 Despite these significant advances in designing heterogeneous FLPs, metal elements are still indispensable for the construction of heterogeneous FLPs, which deviates from the initial metal-free concept of FLP catalysis.…”
Section: Introductionmentioning
confidence: 99%